PRELIMINARY OBSERVATION ON THE USE OF UNDER -WATER LIGHT IN FISH CATCH - BISWAS, K P; MOHANTY, S K (Fishery Technology, 2025)
Experiments with drift gill net] with under-water lights were carried out in the sea and estuarine region along with a control net of the same specifications without any light in the same fishing ground for comparison. The experimental net caught more fish in number and weight than the control. Fishes like pomfrets (Pampus chinensis, Parasfromafeus niger), seer (Scomberomorus spp), hilsa (lfisha spp) etc showed positive phototaxis and were giBed encircling the point of iHumination. Young skates (Mobu!a spp) and Po!ynemus tetradacty! us were antiphototactic. The number of fishes caught increased with increase in period of iHumination. The catch of larger fishes was maximum at 60 mts of i11umination and the total catch increased with increase in intensity of light. Additional cost of operation with under-water light was Rs 1-25 per hr but the catch was 4 to 5 times greater than that of the control net.